Suicide Risk and Association With the Different Trauma During the COVID-19 Pandemic Period: A Cross-Sectional Study on Adolescent With Different Learning Stage in Chongqing, China - Yu, Yao; Wu, Tingting; Wang, Shanshan; Liu, Weiwei; Zhao, Xin (Frontiers in Public Health, 2022)
This study aimed to examine the current suicidal risk and whether the suicidal risk was associated with a wide range of trauma. The self-administered online questionnaire was adopted to collect suicide risk (SR) such as suicidal ideation, self-harm, suicide attempts, and different trauma information of the adolescents by cluster sampling in Chongqing, China. Multivariable linear regression was presented to assess the association between different risks of trauma and SR scores. Approximately 14.7% of adolescents enrolled reported suicide ideation and more than 10% of adolescents have experienced one kind of trauma during the Coronavirus disease 2019 (COVID-19) pandemic period. After adjusting for confounding variables, adolescents who suffered family hurt had a higher risk score of SR (beta coefficients (β) = 0.289, 95% confidence interval (CI) = 0.115–0.463). A positive association was found among participants from junior and senior school (β = 0.415, 95% CI = 0.152, 0.768), and the SR score was positively associated with sexism among participants from the university/college (β = 0.238, 95% CI = 0.042, 0.434). The most potentially obvious trauma that contributed to SR in junior and senior school adolescents might be cyberbullying. Family neglect or abuse might be a detrimental factor in SR for adolescents whether those in junior school or those in university school in China. More interventions, like education related to cyberbullying and family abuse, should be prioritized to reduce the risk of suicide.